DIGITALIZATION OF LOCAL RASHDUL QIBLA BY QIBLA DIAGRAM - Muhammad Thoyfur (Fakultas Syari'ah dan Hukum UIN Walisongo, 2021)
Determination of the direction of qibla develops all the time, starting from the simple way by using the celestial bodies such as the sun with mathematical formulas, using instrumentation such as compasses, rubu'ul mujayyab, mizwala, istiwa'aini, until using the method of combining mathematical formulas and observation tools into digital methods. One method of determining the direction of qibla is Rashdul Qibla method which has two methods, namely Local Rashdul Qibla and Global Rashdul Qibla. This study utilizes the Local Rashdul Qibla method to become instrumentation called Qibla Diagram, this instrumentation is a combination of mathematical calculation in the Microsoft excel program and diagram of Local Rashdul Qibla. This research is a qualitative research based on exploration. Primary and secondary data collection was carried out by experiment and documentation, processed through three stages, namely codification, presentation and conclusions. Then analyze the data using descriptive analysis with the method of inductive thinking. The research resulted in two findings, there are the Microsoft Excel Qibla Diagram calculation program and the Qibla Diagram instrument. The use of the Qibla Diagram is the same as the use of Local Rashdul Qibla, which is local, but the local of the Qibla Diagram has a large enough extent to cover an area of the city and this instrument, digitally, can be used to determine the local Rashdul Qibla throughout the earth's coordinates